Biosorption of Cadmium by fungi isolated from Bharalu river, Assam - Deka, Dipannita; Bora, Pinky; Devi, Nameirakpam Nirjanta; Chabukdhara, Mayuri (Journal of Tropical Life Science, 2021)
Heavy metal pollution in the aquatic ecosystem poses a serious threat to the human health and aquatic biodiversity around. There is urgent need to remediate heavy metals contaminated wastewater through eco friendly ways. Fungi and other microorganisms have been reported to have promising potential to remove heavy metals from wastewater through biosorption. Thus the present work aimed to isolate tolerant fungal species from different sites of a polluted river Bharalu in Assam. After preliminary screening, out of a total of 15 fungal isolates obtained, 4 isolates Aspergillus niger, Aspergillus flavus, Aspergillus fumigates and Colletotrichum gloeosporioides were selected for further study. Tolerance limit of the isolates for Cadmium (Cd) was carried out at concentrations ranging from 100 ppm to 1000 ppm. Results showed that the maximum tolerance was observed in Colletotrichum gloeosporioides (approx. 8.8 mm), followed by Aspergillus flavus (approx. 5.8 mm) at 400ppm. The biosorption efficiency at 400ppm revealed that the maximum Cd concentration was absorbed by fungal biomass of Colletotrichum gloeosporioides (12.83 mg/g) and the minimum by Aspergillus niger (3.91 mg/g). Molecular identification was carried out followed by PCR amplification of the fungal biomass showing highest absorption. The sequence obtained was submitted in the GenBank using BANkIt with accession number-MN714368 which showed high similarities with Colletotrichum gloeosporioides. This results indicated that fungus are promising and potential sources for metal biosorption and detoxification.